Artificial-Intelligence-Based Structural Health Monitoring of Prestressed Concrete Metro Viaducts: A Framework Applied to the Nagpur Metro Elevated Corridor - Dr. Amit Bijon Dutta; Er. Durgesh Shukla (International Journal of Science, Strategic Management and Technology, 2026)
ABSTRACT Urban metro networks across Indian cities, including Nagpur, rely heavily on precast, segmental, prestressed-concrete girders to carry their elevated corridors. Once in service, these girders face repeated dynamic loads from passing trains, continuous exposure to weather, and a slow, ongoing loss of prestress from creep, shrinkage, and tendon relaxation — deterioration that routine visual inspection is poorly suited to catch before it becomes serious. This paper sets out a multi-tier framework for monitoring the structural health of prestressed-concrete metro viaducts using artificial intelligence (AI), combining a mixed sensor network, an edge-to-cloud data pipeline, deep-learning-based damage identification, and digital-twin visualisation. Rather than testing this framework in a laboratory, it is grounded in a real, in-service structure: the elevated viaduct of the Nagpur Metro (Maha-Metro), built mainly from precast segmental box girders and I-girders. The paper traces how SHM practice has developed, draws together AI methods reported in recent literature, and identifies gaps that matter specifically for prestressed-concrete construction, limited explainability of deep-learning models, a shortage of verified in-service datasets, and the difficulty of separating genuine structural change from environmental noise in strain and vibration signals. It then discusses how the proposed framework could map onto a corridor such as Nagpur Metro to support condition-based rather than fixed-schedule maintenance, closing with implementation challenges and directions for future work, including physics-informed learning and edge-based inference for sites with limited connectivity. Keywords: Structural Health Monitoring; Artificial Intelligence; Prestressed Concrete; Metro Viaduct; Digital Twin; Deep Learning; Nagpur Metro